2014
DOI: 10.1038/cddis.2014.23
|View full text |Cite
|
Sign up to set email alerts
|

Arginase 2 deficiency reduces hyperoxia-mediated retinal neurodegeneration through the regulation of polyamine metabolism

Abstract: Hyperoxia treatment has been known to induce neuronal and glial death in the developing central nervous system. Retinopathy of prematurity (ROP) is a devastating disease in premature infants and a major cause of childhood vision impairment. Studies indicate that, in addition to vascular injury, retinal neurons are also affected in ROP. Using an oxygen-induced retinopathy (OIR) mouse model for ROP, we have previously shown that deletion of the arginase 2 (A2) significantly reduced neuro-glial injury and improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
92
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(101 citation statements)
references
References 59 publications
9
92
0
Order By: Relevance
“…32 We performed TUNEL analysis to determine whether the larger avascular region in WT mice at P12 was attributed to neuronal and endothelial apoptosis. Consistent with other studies, [33][34][35] TUNEL-positive signals were detected within the inner nuclear layer (INL; mainly neurons such as amacrine cells and bipolar cells) and outer nuclear layer (ONL) of the avascular area, as well as the ganglion cell layer (GCL) of both WT and A 1 R KO groups. Furthermore, TUNEL signal was detected in both INL and ONL layers but largely segregated from the CD31 þ cells (a marker for endothelium cells) with only very few TUNEL/CD31 costaining signals, indicating that apoptosis was mainly attributed to neuronal apoptosis in retina (Figs.…”
Section: Genetic Deletion Of a 1 Rs Reduced Hyperoxiainduced Retinal supporting
confidence: 71%
“…32 We performed TUNEL analysis to determine whether the larger avascular region in WT mice at P12 was attributed to neuronal and endothelial apoptosis. Consistent with other studies, [33][34][35] TUNEL-positive signals were detected within the inner nuclear layer (INL; mainly neurons such as amacrine cells and bipolar cells) and outer nuclear layer (ONL) of the avascular area, as well as the ganglion cell layer (GCL) of both WT and A 1 R KO groups. Furthermore, TUNEL signal was detected in both INL and ONL layers but largely segregated from the CD31 þ cells (a marker for endothelium cells) with only very few TUNEL/CD31 costaining signals, indicating that apoptosis was mainly attributed to neuronal apoptosis in retina (Figs.…”
Section: Genetic Deletion Of a 1 Rs Reduced Hyperoxiainduced Retinal supporting
confidence: 71%
“…Both isoforms are also expressed in retina. Prominent immunoreactivity for A1 is evident in retinal glia [64, 65] and A2 is abundant in horizontal cells, photoreceptor inner segments and cellular processes throughout the neural retina, consistent with its mitochondrial localization [66, 67]. …”
Section: Arginase and Cns Disease/injurymentioning
confidence: 91%
“…Partial deletion of A1 along with A2 did not confer any additional protection, suggesting that A2 is the more important isoform involved in the neurodegeneration. Further studies demonstrated increased expression of spermine oxidase together with decreases in spermine, increases in spermidine and increases in hydrogen peroxide formation in the OIR retina compared to normoxic controls, suggesting an increase in backward polyamine catabolism (Figure 4) [67]. These alterations were significantly reduced in the A2-deficient OIR retina.…”
Section: Arginase and Cns Disease/injurymentioning
confidence: 99%
“…In addition, studies have shown that PAOs and acrolein can serve as novel biomarkers for diagnosis of cerebral stroke [34,35]. Our studies recently highlighted the role of polyamine metabolism in causing retinal neuronal degeneration [36]. However, the role of PAO in retinal vascular injury is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Our studies showed that hyperoxia-induced neuronal degeneration is associated with significant increase in function of PAOs and expression of SMO. This was associated with increases in spermidine and H 2 O 2 and decreases in spermine, suggesting a significant role for SMO in the neuronal injury [36]. Studies in transgenic mice overexpressing SMO in neonatal cortex have shown increased levels of H 2 O 2 and increased sensitivity to excitotoxic brain injury [38].…”
Section: Introductionmentioning
confidence: 99%